Introduction of Innovative Technologies Into Practice of Strategic Management of A Company In Terms of Entering The International Market - Xiuxiu Gao; Natalia Sakharchuk (Communications of International Proceedings, 2022)
The personal care industry is undergoing many global changes. These changes are shaping the need for open innovation in medium-sized companies and well-known global brands. Companies that introduce innovative technologies into business have a great future in world markets. Today, a large number of companies know that they must innovate in their business in order to lead the market and generate greater profits. Most business professionals agree that innovation is critical to their success. 90% of executives believe that the long-term success of a company's strategy depends on their ability to develop new ideas. Today's innovative companies are rewarded for being ready for the future, for outstanding talent and increased customer demand. Experts estimate that the global personal care market will surpass more than $ 650 billion by 2024. This was influenced by the pandemic. People are increasingly taking care of their health and buying antibacterial agents. In the United States alone, the market for personal care products exceeds $ 36 million a year. Its annual growth rate is 9.3%. Market consumers account for 28.3% and the market is expected to grow to 33.1% by 2022. The Asia-Pacific region has the largest market share and will maintain its dominant presence in the world market in the coming years.
Keywords: innovations; strategies; branding; innovative technologies; production